Prophetic Leadership Khulafaur Rosyidin - Yuni Masrifatin (EDUTEC : Journal of Education And Technology, 2018)
Leadership is a mandate and therefore, in an Islamic system, one must not demand a position. Leaders have a very important position for community groups, nation and state. A community, nation and state will not advance, safe and directed if there is no leader. Leaders become the key to success in a community, leaders who are able to provide a sense of security, peace, and able to realize the wishes of their people, that is what is considered a successful leader. Successful leaders are leaders who are loved by those they lead, so their minds are always supported, their orders are always followed and the people defend them without being asked first. The leadership figure that approaches this explanation is the leadership of the Prophet and his companions (Khulafaur Rasyidin). Abu Bakr was chosen to be the caliph to replace leadership after the Messenger of Allah was a blessing in itself, and this kind of privilege was given to him by Allah. Basically the companions of the Prophet are people who will inherit Islamic da'wah / treatise for all mankind, as well as being a leader for themselves with their exemplary example and the Islamic faith in carrying out the shari'ah of Allah Almighty and His Rasul, both through the book of Allah and the sunnah of the Messenger of Allah. In this paper, it will be discussed how the leadership progress in the Khulafaur Rosyidin period, as long as a leader, the problems faced as well as the progress that has been achieved in fighting for and expanding the Islamic territory, so that Islam can be glorious at that time.